Kinerja Dinas Kependudukan Dan Pencatatan Sipil Dalam Pelayanan Administratif Di Kabupaten Lamongan - Yustisia Pradhana Arie Sandya (Jurnal Administrasi Publik, 2013)
Abstract: Performance of Population and Civil Registration In Administrative Services In Lamongan. In carrying out the functions of both the government and the bureaucratic organization must be professional, responsive, aspiring to the various demands of the community served. Both the poor performance of the organization would be influenced by the factors that support or hinder the performance of an organization such as the internal factors or human resource officers who are in the Department of Population and Civil Registration them. Organizational performance is associated with the inputs, outputs, and outcomes that have been generated by a so organisasai Department of Population and Civil Registration priority outputs and outcomes are always effective and can give feedback to be used as input in the evaluation and improvement of the district's authority in the field menyelenggaraan Implement Services In the administrative Lamongan. Research Objectives To describe and analyze the performance of the organization's Office of Population and Civil Registration in administrative services in Lamongan. To describe and analyze the factors supporting and inhibiting factors the performance of the Department of Population and Civil Registration in administrative services. Types of research used in this research is descriptive research using a qualitative approach. it can be concluded that the Main Task and function of Population and Civil Registration Lamongan is held governmental affairs and public service population and civil registration. In carrying out servicing legal documents and Acts of civil records, carried out with the program SIAK ofline. Performance of the Office of Population and Civil Registration Lamongan in performing administrative services has lead to the realization of effective service, efficiently and economically. Keywords: Performance, Department of Population and Civil Registration, Administrative Services. Â  Abstrak: Kinerja Dinas Kependudukan Dan Pencatatan Sipil Dalam Pelayanan Administratif di Kabupaten Lamongan. Dalam melaksanakan fungsi pemerintah dengan baik maka organisasi birokrasi harus professional, tanggap, aspiratif terhadap berbagai tuntutan masyarakat yang dilayani. Baik buruknya kinerja organisasi tentu dapat dipengaruhi oleh adanya faktor yang mendukung atau menghambat kinerja organisasi antara lain faktor intern yaitu aparat atau sumber daya manusia yang berada di dalam Dinas Kependudukan Dan Pencatatan Sipil tersebut. Kinerja organisasi sangat berhubungan dengan input, output, dan outcomes yang telah dihasilkan oleh suatu organisasai sehingga Dinas Kependudukan Dan Pencatatan Sipil selalu mengutamakan output dan outcomes yang berdaya guna dan dapat memberi timbal balik untuk dijadikan bahan evaluasi dan perbaikan input dalam menyelenggaraan kewenangan kabupaten dibidang Â melaksanakan pelayanan administratif di Kabupaten Lamongan. Tujuan Penelitian Untuk mendeskripsikan dan menganalisis kinerja organisasi Dinas Kependudukan Dan Pencatatan Sipil dalam pelayanan administratif di Kabupaten Lamongan. Untuk mendeskripsikan dan menganalisis faktor pendukung dan faktor penghambat kinerja Dinas Kependudukan Dan Pencatatan Sipil dalam pelayanan administratif. Jenis penelitian yang digunakan dalam penelitian ini adalah jenis penelitian deskriptif dengan menggunakan pendekatan kualitatif. dapat disimpulkan bahwa Tugas Pokok serta fungsinya Dinas Kependudukan dan Pencatatan Sipil Kabupaten Lamongan yaitu menyelenggarakan urusan Pemerintahan dan pelayanan umum bidang kependudukan dan pencatatan sipil. Dalam melaksanakan pelayanan dokumen kependudukan dan dan Akta- akta catatan sipil, dilaksanakan dengan program SIAK ofline. Kinerja dari Dinas Kependudukan dan Pencatatan Sipil Kabupaten Lamongan dalam melaksanakan pelayanan administratif ini telah mengarah pada terwujudnya pelayanan yang efektif, efisien dan ekonomis. Kata Kunci : Kinerja, Dinas Kependudukan dan Pencatatan Sipil, Pelayanan administratif.